Abnormal keratinization and cutaneous inflammation in Mal de Meleda. Issue 5 (10th March 2020) - Kudo, Mari; Ishiura, Nobuko; Tamura‐Nakano, Miwa; Shimizu, Teruo; Kamata, Masahiro; Akasaka, Eijiro; Nakano, Hajime; Okuma, Yoshiaki; Tada, Yayoi; Okochi, Hitoshi; Tamaki, Takeshi
Abstract: Mal de Meleda (MDM) is a rare, autosomal recessive form of palmoplantar keratoderma due to mutations in the gene, encoding for secreted lymphocyte antigen 6/urokinase‐type plasminogen activator receptor related protein 1 (SLURP1). We report a four‐year‐old Taiwanese MDM female case whose biopsy specimen of hyperkeratotic lesions showed abnormal keratinization and cutaneous inflammation with characteristic transmission electron microscopic (TEM) findings and immunostaining results. The patient presented with pruritic and severely hyperkeratotic plaques on the bilateral palms and soles whichwere fringed with erythematous scaly areas. A homozygous c.256 G>A mutation, predicting a conversion of p.Gly86Arg, in SLURP1 gene was detected. Histopathological examinations showed marked hyperkeratosis, acanthosis and hypergranulosis in the epidermis, accompanied by perivascular lymphocytic infiltrates in the dermis. The whole layers of the epidermis and perivascular infiltrates of the dermis were stained positive with anti‐tumor necrosis factor alpha (TNFα) antibody in the biopsy specimen from the sole and the ankle. TEM examination of the biopsy specimen from the plantar hyperkeratotic plaque showed various‐sized vacuoles surrounding nuclei of many keratinocytes in the spinous layer. In addition, there were numerous irregular keratohyaline granules in the granular layer. Several microorganisms and many lipid‐like droplets were found in the thickened cornified layer. SLURP1 protein is known as a marker of late differentiation, predominantly expressed in the granular layer, and also known to have an inhibitory effect on TNFα release. Our results exhibited excessive TNFα expression in keratinocytes and perivascular infiltrates of the dermis, and several characteristic morphological observations of keratinocytes in MDM.